2012
DOI: 10.1017/s0963548312000570
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Arrays of Odd Order by Latin Squares

Abstract: We prove that there is a constantcsuch that, for each positive integerk, every (2k+ 1) × (2k+ 1) arrayAon the symbols (1,. . .,2k+1) with at mostc(2k+1) symbols in every cell, and each symbol repeated at mostc(2k+1) times in every row and column isavoidable; that is, there is a (2k+1) × (2k+1) Latin squareSon the symbols 1,. . .,2k+1 such that, for eachi,j∈ {1,. . .,2k+1}, the symbol in position (i,j) ofSdoes not appear in the corresponding cell inA. This settles the last open case of a conjecture by Häggkvist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 9 publications
0
42
0
Order By: Relevance
“…, n})-list assignment 1 for L(K n,n ), then whp there is an L-coloring of L(K n,n ). Note that in [1] this result is formulated in the language of arrays and Latin squares.…”
Section: Introductionmentioning
confidence: 99%
“…, n})-list assignment 1 for L(K n,n ), then whp there is an L-coloring of L(K n,n ). Note that in [1] this result is formulated in the language of arrays and Latin squares.…”
Section: Introductionmentioning
confidence: 99%
“…This theorem is proved in Section 2. It is actually an easy consequence of a stronger result of Andrén, Casselgren, and Öhman [2], who showed that an analogous minimum-degree result holds. We include it here because the proof is short and elegant.…”
mentioning
confidence: 84%
“…There are some previous results on coloring graphs from random lists of nonconstant size in the literature: In , it is proved that there is a constant c > 0 such that if L is a random (k,{1,,n}) ‐list, assignment for L(Kn,n), where L(Kn,n) is the line graph of the balanced complete bipartite graph on n + n vertices and k>(1c)n, then whp there is an L ‐coloring of L(Kn,n). Note that in this result is formulated in the language of arrays and Latin squares.…”
Section: Random Lists Of Nonconstant Sizementioning
confidence: 99%
“…In this section, we demonstrate how the methods from Sections 2 and 3 can be used for proving some analogous results on list coloring when the size k of the lists in a random (k, C)-list assignment is a (slowly) increasing function of n. We shall derive such analogues of several of the results in the preceding sections. There are some previous results on coloring graphs from random lists of nonconstant size in the literature: In [2], it is proved that there is a constant c > 0 such that if L is a random (k, {1, . .…”
Section: Random Lists Of Nonconstant Sizementioning
confidence: 99%
See 1 more Smart Citation